2017
DOI: 10.1021/acs.energyfuels.7b01345
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Fuel Composition Impact on Black Carbon Mass, Particle Number Size Distributions, Solid Particle Number, Organic Materials, and Regulated Gaseous Emissions from a Light-Duty Gasoline Direct Injection Truck and Passenger Car

Abstract: The influence of the aromatic hydrocarbons in gasoline on the fuel distillation parameter, as well as the particle number (PN), black carbon (BC), and other regulated gaseous emissions from a passenger car (PC) and light-duty truck (LDT), was assessed by operating two vehicles fueled with U.S. Environmental Protection Agency Tier 3 certification gasoline and two gasoline test fuels over two standard drive cycles. The two gasoline test fuels represent a range of commercial motor gasoline, with one containing le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…This will likely result in a poor air–fuel mixture and diffusion combustion (pool fire) of liquid fuel, leading to higher soot emissions. Previous studies have also shown increased particulate emissions with higher aromatic content gasoline fuels. , ,, …”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This will likely result in a poor air–fuel mixture and diffusion combustion (pool fire) of liquid fuel, leading to higher soot emissions. Previous studies have also shown increased particulate emissions with higher aromatic content gasoline fuels. , ,, …”
Section: Resultsmentioning
confidence: 90%
“…Previous studies have also shown increased particulate emissions with higher aromatic content gasoline fuels. 5,[8][9][10]46,47 Figure 5 and Figure 6 illustrate the particle size distribution characteristics for all test fuels over the cold-start and hot-start LA92s, respectively. For most fuels, the particle size distributions showed bimodal profiles, consisting of a nucleation mode (10−23 nm) and an accumulation mode (23−100 nm).…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Compared to other market fuels in the literature, our fuel had one of the highest PM index and Moriya values [40,41]. Studies with higher values (2.5-2.9) are limited [38,89]. Very high values (e.g., PM index of 3.2) have been tested at studies evaluating various indexes; these fuels were specifically blended for the specific studies [43].…”
Section: Methodsmentioning
confidence: 99%
“…The regeneration of soot can lead to breakage of the soot cake layer, which will reduce the filtration efficiency. However, in most driving conditions and life periods of a vehicle, the filtration efficiency of the GPF is expected to be very high (>90%) [16].The filter element is the key component to determining the performance of the GPF, so the material selection and structure design of the filter element are very important.Cordierite is commonly used in traditional filter element materials. It has a low thermal expansion coefficient and good thermal shock performance, which makes it a mature material for both flow-through substrates and wall-flow filters [17,18].…”
mentioning
confidence: 99%
“…The regeneration of soot can lead to breakage of the soot cake layer, which will reduce the filtration efficiency. However, in most driving conditions and life periods of a vehicle, the filtration efficiency of the GPF is expected to be very high (>90%) [16].…”
mentioning
confidence: 99%